ANAK-ANAK SEBAGAI KORBAN KEJAHATAN SEKSUAL DARI ORANG DEWASA - Antoni Antoni (Nurani, 2015)
Abstract: The child is a time of joy and excitement and this is where the future growth and small flowers . On the other hand violence done to children is common. A series of sexual abuse of children is not just a physical mark on their little bodies, but also to make an impression in the soul of a child until he grew up. One day later not blame them, when they tend to do things that deviate. This article will discuss the position of the child as an object of sexual violence legal philosophy perspective ملخص: الطفولة ھي فترة من الفرح والإثارة وھذا ھو المكان نمو و أزھار الطفولة في المستقبل. على العنف جھة أخرى القیام بھ للأطفال شائعة. وھناك سلسلة من الاعتداء الجنسي على الأطفال لیس فقط أن یكون بصمة جسدیا على أجسادھم الصغیرة، ولكن أیضا جعل انطباعا في النفس للطفل حتى نشأ وترعرع. في وقت لاحق یوم واحد لا ألومھم، عندما تمیل إلى فعل الأشیاء التي تحید. ھذه المادة سوف یناقش وضع الطفل ككائن العنف الجنسي منظور الفلسفة القانونیة. Kata Kunci: Kejahatan terhadap anak